Non-cooperation of the promisee in breach of contract in Iranian and European law - Mohammad Taqi Rafiei; Seyed Hossein Hejazi (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2022)
When a contract is not entered into the implementation stage or in the implementation of the work, it stops or does not comply with the contractual terms and conditions and the agreed specification is diverted, the magistrate at the beginning, the arrow is committed to understand and ask him about the breach of commitment and the cause of its deviation from the terms of the contract, so that one can predict his conviction from the beginning. In Iran's law, it is less attentive that the violation of the Treaty may be disabled for non-cooperation of the obligee, while the implementation of qualifier commitment may be on his cooperation. Where the obligee would have to deliver the project's location to establish a workshop, or the client will submit the principles of documents, information and witnesses ' names, or the disease that should be carried out by the doctor before the surgery, all the anath of the implementation of a commitment to the Obligee's cooperation. This cooperation can sometimes be defined as a verb, leaving the verb, submitting the goods or documents, providing services and information, resulting in a lack of cooperation, a contract with a challenge and a bug. Rationals and will logically and the implementation of the contract shall be subject to the obligee's cooperation, but the question is to mind whether this cooperation should be stipulated in the contract or a marriage is concluded or is considered as a contract of marriage and customary equipment. Unlike Iran's legal and judicial literature, the role of the obligee cooperation in European countries ' rights and European legal documents has been approved and various works have been predicted for his non-cooperation.  In this paper, in addition to the legal foundations of such a commitment, the various legal effects of its breach are investigated so that the sum of them can be explained most of the role of this cooperation.